SOCIAL MEDIA USAGE BEHAVIOR AND ITS EFFECT ON MUSLIM COMMUNITY ANXIETY IN FACING THE COVID-19 PANDEMIC IN MEDAN CITY - Hani, Syafrida; Juliandi, Azuar; Irfan, Irfan (Proceeding International Seminar of Islamic Studies, 2024)
The problems identified in this study are: (1) the Corona Virus or Covid-19 has become symptomatic in the world, including in Indonesia; (2) The public knows that information on Covid-19 comes from the mass media; (3) Scientific studies show that mass media is able to create a positive impact, but it can also have a negative impact on society, namely anxiety, depression and other mental health disorders, especially during the Covid-19 period. For these problems, this study aims to analyze the effect of social media use behavior in influencing the creation of public anxiety in the face of the Covid-19 pandemic. This research method uses a survey design to 666 Muslim respondents in Medan. Collecting research data is a questionnaire about the behavior of using social media and public anxiety. Analysis of research data using inferential statistical analysis with Structural Equation Model-Partial Least Square (SMART-PLS). This study produced several findings, including: First, the behavior of people in using social media during the Covid-19 pandemic was generally quite high; Second, the level of public anxiety facing the Covid-19 pandemic generally also shows a fairly high level; and Third, the behavioral effect of using social media in influencing the creation of public anxiety in the face of the Covid-19 pandemic appears to have a significant effect.